2022
DOI: 10.1021/acs.est.1c01739
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Data Analytic and Modeling Methods to Support Air Pollution and Environmental Justice Investigations: A Critical Review and Guidance Framework

Abstract: Given the serious adverse health effects associated with many pollutants, and the inequitable distribution of these effects between socioeconomic groups, air pollution is often a focus of environmental justice (EJ) research. However, EJ analyses that aim to illuminate whether and how air pollution hazards are inequitably distributed may present a unique set of requirements for estimating pollutant concentrations compared to other air quality applications. Here, we perform a scoping review of the range of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 192 publications
0
28
0
Order By: Relevance
“…For example, a number of studies have found that air pollution exposure could be impacted by small-scale differences in the built environment, including traffic and road geometry [ 67 ], impervious surface [ 68 , 69 ], greenness [ 70 ], walkability [ 71 ], the fragmentation of urban patches [ 70 ], and other factors [ 19 , 72 , 73 , 74 ]. Oftentimes, disadvantaged communities are near highways, have much fewer green spaces, much greater auto dependence, poor quality pavement streets, and residential segregation patterns [ 14 , 46 , 48 ], which may be associated with adverse air pollution exposure [ 73 ] and disparities [ 75 ]. Without increased air monitoring networks among disadvantaged communities, one cannot explore such mechanisms, thus failing to eliminate built environment disparities [ 76 ], conduct air pollution exposure assessment [ 77 ], inform emission control strategies [ 43 ], and assess public health outcomes [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of studies have found that air pollution exposure could be impacted by small-scale differences in the built environment, including traffic and road geometry [ 67 ], impervious surface [ 68 , 69 ], greenness [ 70 ], walkability [ 71 ], the fragmentation of urban patches [ 70 ], and other factors [ 19 , 72 , 73 , 74 ]. Oftentimes, disadvantaged communities are near highways, have much fewer green spaces, much greater auto dependence, poor quality pavement streets, and residential segregation patterns [ 14 , 46 , 48 ], which may be associated with adverse air pollution exposure [ 73 ] and disparities [ 75 ]. Without increased air monitoring networks among disadvantaged communities, one cannot explore such mechanisms, thus failing to eliminate built environment disparities [ 76 ], conduct air pollution exposure assessment [ 77 ], inform emission control strategies [ 43 ], and assess public health outcomes [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is an urgent need for guidance on quantifying air pollution exposure disparities, due to rapid evolution of data (e.g., from satellites, models, and low-cost sensors) and to growing momentum in efforts to measure, track, and address such disparities (e.g., from US state environmental justice policies , and screening tools , ). Analytic challenges in doing so include the definition of disparity metrics, the collection of air pollution and demographic data, the method of exposure assessment, and the spatial scale of data aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing equity concerns requires a standardized framework of methods of analysis and hence an improved understanding of environmental health disparities. 25 Both cross-national collaboration and communitybased participatory research are critical to address global and local disparities in the health burden of air pollution and foster corrective action on inequalities. Low-cost air sensors can be one of the effective measures to empower low-income countries and underprivileged communities to improve their air quality monitoring infrastructure.…”
Section: ■ Moving Forwardmentioning
confidence: 99%
“…There is also an enhanced appreciation in environmental policy of the desirability of pursuing environmental equity. Addressing equity concerns requires a standardized framework of methods of analysis and hence an improved understanding of environmental health disparities . Both cross-national collaboration and community-based participatory research are critical to address global and local disparities in the health burden of air pollution and foster corrective action on inequalities.…”
Section: Moving Forwardmentioning
confidence: 99%